Thoracic Aortic Emergencies: Presenting Pathologies and Treatment Strategies - Sheeran, Daniel P.; Zelickson, Adam M.; Wilkins, Luke R.; Angle, J. Fritz; Williams, David M.; Khaja, Minhaj S. (Seminars in Interventional Radiology, 2020)
Thoracic aortic emergencies reflect a wide range of etiologies, pathologic processes, and clinical presentations. Accurate identification with an appropriate treatment algorithm is best accomplished in a multidisciplinary setting with interventional radiologists, vascular surgeons, and cardiothoracic surgeons. While knowledge of thoracic stent graft equipment and technique is essential in the treatment of thoracic aortic emergencies, many clinical settings may employ alternative treatment techniques. This article will review the most common thoracic aortic emergencies and treatment strategies.
Keywords: TEVAR; fenestration; aortic dissection; traumatic aortic injury; interventional radiology